Penyuluhan Kesehatan tentang Pijat Oksitosin Pada Ibu Hamil Trimester II dan III - Herlinda, Herlinda; Widyaningsih, Sari (JURNAL BESEMAH, 2023)
Oxytocin massage is massage along the spine (vertebrae) to the fifth-sixth costae and is an attempt to stimulate the hormones prolactin and oxytocin after childbirth. Oxytocin massage is one of the solutions to overcome non-smooth milk production, reduce engorgement and reduce breast milk blockage. Oxytocin is what can calm the mother, so that the milk comes out automatically. Midwives, husbands or family members are people who can help mothers in providing oxytocin massage therapy. The purpose of this community service is to increase the knowledge and skills of mothers, husbands and family members in preparing pregnant women so that the production and release of breast milk runs smoothly. The method used is counseling and demonstration or practice of implementing oxytocin massage. From the community service activities that were carried out at the Prosperous Posyandu in the Work Area of ​​the Jalan Gedang Health Center in August 2023 for 15 pregnant women, it was found that there were still pregnant women who did not know about the importance of exclusive breastfeeding, Oxytocin Massage and how to practice it. Massage is done for about 5 minutes with 5 actions or massage on the backKeywords: Oxytocin Massage, Pregnant Women TM II and III